The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.18632/oncotarget.22192
|View full text |Cite
|
Sign up to set email alerts
|

Sensitization of lung cancer cells by altered dimerization of HSP27

Abstract: Heat shock protein 27 (HSP27, HSPB1) induces resistance to anticancer drugs in various cancer types, including non-small cell lung cancer (NSCLC). Therefore, pharmacological inhibition of HSP27 in NSCLC may be a good strategy for anticancer therapy. Unlike other HSPs such as HSP90 and HSP70, small molecule approaches for neutralization of HSP27 are not well established because of the absence of an ATP binding domain. Previously, small molecules with altered cross linking activity of HSP27, were identified to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 24 publications
2
26
0
Order By: Relevance
“…Despite studies showing that quercetin can be a suitable agent for cancer treatment, there are no ongoing anticancer trials for quercetin. J2, a synthetic chromone compound, can induce the crosslinking of HspB1 protein and form HspB1 abnormal dimerization, thereby inhibiting its functions [160]. Recently, ovatodiolide [132] and methyl antcinate [161], two plant-derived compounds, have been reported to decrease HspB1 protein expression in breast CSCs and inhibit CSCs.…”
Section: Anticancer Drugs Targeting Shspsmentioning
confidence: 99%
“…Despite studies showing that quercetin can be a suitable agent for cancer treatment, there are no ongoing anticancer trials for quercetin. J2, a synthetic chromone compound, can induce the crosslinking of HspB1 protein and form HspB1 abnormal dimerization, thereby inhibiting its functions [160]. Recently, ovatodiolide [132] and methyl antcinate [161], two plant-derived compounds, have been reported to decrease HspB1 protein expression in breast CSCs and inhibit CSCs.…”
Section: Anticancer Drugs Targeting Shspsmentioning
confidence: 99%
“…Moreover, the altered dimerization of HSP27 can sensitize cancer cells with high HSP27 expression [32]. This strategy is expected to overcome drug development currently limited by the absence of HSP27 inhibitors and presents the possibility of the development of novel HSP27 inhibitors (Fig.…”
Section: The Role Of Hsp27 In Cancermentioning
confidence: 99%
“…According to recent studies, zerumbone [45], isolated from a natural product, and SW15, a xanthone compound sensitized cancer cells in combination with radiation. J2, a synthetic chromone compound, has a pharmacophore structure and more potent cross-linking activity than SW15 [32]. Therefore, the alteration of cross-linking is considered to be a novel strategy for the Preprints (www.preprints.org) | NOT PEER-REVIEWED | Posted: 4 July 2019 doi:10.20944/preprints201907.0081.v1…”
Section: Altered Dimerization Of Hsp27 Using Small Moleculesmentioning
confidence: 99%
See 1 more Smart Citation
“…The SNPs of HSPB1 rs7459185 was associated with radiation esophagitis in lung cancer through the regulation of HSPB1 expression level (Delgado et al, 2019). HSPB can regulate aggressive tumor behavior, metastasis, poor prognosis, and resistance to chemotherapy through the interference with theses effectiveness of targeted agents (Choi et al, 2017). There was one report about HSPB polymorphism found to be associated with NSCLC prognosis, in the US patients, it found that the CC genotype of HSPB1 rs2868371 was associated with poorer overall survival in US patients with NSCLC after radio (chemo)therapy (Xu et al, 2012).…”
mentioning
confidence: 99%